Pelestarian Budaya Melayu Lokal Melalui Ekstrakulikuler Seni Tari Rentak Bulian di SMA Negeri 1 Seberida Kabupaten Indragiri Hulu - Deltya Mifta Ulrahma; Yahyah Erawati (Abstrak : Jurnal Kajian Ilmu seni, Media dan Desain, 2025)
This study aims to increase the author's knowledge and insight. While the goal is to collect and solve every problem found by researchers specifically describing the preservation of local Malay culture through extracurricular dance arts rentak bulian at Sma Negeri 1 Seberida Indragiri Hulu Regency. In this study, the researcher uses Sedyawati's theory (2007) which discusses protection, utilization, development. This type of research is qualitative. The method used in this study is a descriptive qualitative method, namely observation, interviews and documentation. The author made observations and then interviewed several sources. The author reviewed the documentation of the information data that the author had obtained. The results of this study indicate that in the implementation of dance extracurricular activities at Sma Negeri 1 Seberida. In the preservation of Rentak Bulian dance at SMAN 1 Seberida, protection is carried out by providing extracurricular dance activities, starting from costumes, make-up, properties are also preserved in the provision of this extracurricular activity, the development of preservation by presenting dance not only for healing ceremonies but also for entertainment events and competitions. As well as utilization to support student abilities and consciously introduce Rentak Bulian dance to the community so that the existence of the dance is not lost